The Effect of Cooperative Learning on Learning Motivation: A Meta-Analysis - Eka Damayanti; Fitriani Nur; Santih Anggereni; Ainul Uyuni Taufiq (Buletin Psikologi, 2023)
Cooperative learning can increase students' learning motivation. Numerous studies have examined the effect of these models on students' motivation to learn. This meta-analysis study was designed to generalize the impact on science learning motivation in elementary, junior high, and senior high school students. This study aims to examine the effect of cooperative learning models on students' learning motivation at the elementary, junior high, and high school levels, as well as the difference in mean motivation scores between the control and experimental groups. This study was conducted using meta-analysis techniques. The data used in this study came from 13 previous studies. The data were then analyzed using descriptive and inferential statistics. The research findings revealed that the effect of the cooperative learning model on learning motivation at the junior high school level was greater than that at other educational levels. Additionally, there was no discernible difference in the mean motivation score between the experimental group using the cooperative learning model and the control group using the conventional learning model.